Nitrogen and Potassium Exchange in an Acid Tropical Soil Incorporated with Synthetic and Natural Zeolites - Ilias, Zubaidah (2002)
Generally, soils in the tropics are highly weathered, acidic and low in fertility status. High precipitation and low soil cation exchange capacity (CEC) require large amounts of fertilization and liming to ameliorate and increase the potential of these soils. Leaching losses of NH4 + and K+ are extremely large in tropical soils. Zeolites are natural clay silicates that have high affinity and ability to adsorp NH4 + and K+. They are able to release these ions gradually. A study was carried out in three parts. Experiment I was conducted to determine the chemical characteristics of natural and synthetic zeolites. The result of this study suggested that the materials used were zeolites and therefore can be used for further experiment. Experiment II was conducted to determine the adsorption characteristics of NH4 + and K+ by the natural and synthetic zeolites. The result showed that treatment with synthetic Zeolite A (ZA), and natural zeolite (namely Clinop I, from Malang, Indonesia and Clinop II from Sweetwater County, Wyoming, USA) reduced leaching of K+ and NH4 +. The zeolites treatm'ents'increased 2-3 times higher the CEC of the soils after 20 days of incubation. Natural zeolites treatments were better than the synthetic zeolite in retaining exchangeable cation. Experiment III was conducted to evaluate the efficacy of NH/ and K+ retained in the soil using corn (var. Putra 1-58) as a test crop planted for 56 days. The results showed there were significant differences between the zeolites treatment and the control for K and N concentration in the plant tissue. The application of K+ and NH4 + saturated zeolites increased the soil CEC about 2-3 times higher. However, there was no significant difference in dry matter yield and root weight. This study showed that zeolite can be used as a soil amendment to overcome low CEC soils and leaching losses of NH4 + and K+ on highly weathered soils.